2019
DOI: 10.1089/jpm.2018.0202
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association between Healthcare Utilization and Clinical Characteristics among Cancer Patients in a Safety Net Health System

Abstract: Objective-The goal of this study was to examine the association between available patient and clinical characteristics and healthcare utilization in a cohort of breast, lung, and colorectal cancer patients within a safety-net hospital system. Methods-Data for 979 breast, lung, and colorectal cancer patients admitted to a large, urban hospital for the year 2010 were extracted from the electronic medical record (EMR). Univariate and multivariate logistic regression analyses were performed to examine the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Given the nature of the study question, we cannot assume that questionnaire response patterns alone were indicative of future healthcare utilization. Within the included study sample, few analyses controlled for well‐known prognostic factors like disease severity and presence of comorbidities that may contribute to healthcare utilization 65,66 . Additionally, healthcare utilization was defined broadly in the current review, therefore, there was heterogeneity in the definition and measurement of the outcome variable of interest which also limits our ability to generalize the current results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the nature of the study question, we cannot assume that questionnaire response patterns alone were indicative of future healthcare utilization. Within the included study sample, few analyses controlled for well‐known prognostic factors like disease severity and presence of comorbidities that may contribute to healthcare utilization 65,66 . Additionally, healthcare utilization was defined broadly in the current review, therefore, there was heterogeneity in the definition and measurement of the outcome variable of interest which also limits our ability to generalize the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Within the included study sample, few analyses controlled for well-known prognostic factors like disease severity and presence of comorbidities that may contribute to healthcare utilization. 65,66 Additionally, healthcare utilization was defined broadly in the current review, therefore, there was heterogeneity in the definition and measurement of the outcome variable of interest which also limits our ability to generalize the current results. As measurement of healthcare utilization is pertinent to national policy, cancer center rankings, and accreditation standards (e.g., hospital readmission rates post-surgery or post-chemotherapy), well-controlled prospective studies utilizing electronic health record data as well as validated healthcare utilization questionnaires 67 are warranted to further explore this relationship.…”
Section: Limitations and Needs For Future Researchmentioning
confidence: 99%
“…Some studies found that hospice enrolment was involved in a 1.5-2 fold decrease in ED attendances 13,37,38 . Patients who had access to specialist palliative care teams were less likely to attend ED than patients without palliative care access 18,39 .…”
Section: Enrolment In Hospice Programmementioning
confidence: 98%
“…There was more heterogeneity in the findings associated with race (4 studies), and rurality (5 studies). The majority of studies that examined race/ethnicity reported that cancer decedents with non-white ethnicity were more likely to use unscheduled care compared to those of white ethnicity 10,14,18,19 . While there were some conflicting results 16 , most studies reporting on rurality found that cancer decedents who lived living in an urban setting were more likely to use the ED than those who lived in rural or semi-rural areas 10,11,13,16 .…”
Section: Demographymentioning
confidence: 99%
See 1 more Smart Citation